2019
DOI: 10.5603/arm.2019.0051
|View full text |Cite
|
Sign up to set email alerts
|

Current Treatment Strategies in Malignant Pleural Mesothelioma with a Treatment Algorithm

Abstract: Malignant pleural mesothelioma (MPM) is a rare disease with a poor prognosis. The main therapeutic options for MPM include surgery, chemotherapy, and radiation therapy (RT). Although multimodality therapy has been reported to improve survival, not every medically operable patient is able to undergo all recommended therapy. With improvements in surgical techniques and systemic therapies, as well as advancements in RT, there has been a potential new paradigm in the management of this disease. In this review, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 95 publications
0
9
0
Order By: Relevance
“…Surgical procedures such as extrapleural pneumonectomy (EPP) and pleurectomy/decortication have been proposed as curative or palliative approaches, respectively. 13–15 However, the clinical outcome of the mesothelioma and radical surgery (MARS) trial suggested that EPP within trimodal therapy has no benefit. 16 The benefit of open pleurectomy/decortication in addition to chemotherapy is currently under investigation in the MARS 2 trial.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Surgical procedures such as extrapleural pneumonectomy (EPP) and pleurectomy/decortication have been proposed as curative or palliative approaches, respectively. 13–15 However, the clinical outcome of the mesothelioma and radical surgery (MARS) trial suggested that EPP within trimodal therapy has no benefit. 16 The benefit of open pleurectomy/decortication in addition to chemotherapy is currently under investigation in the MARS 2 trial.…”
Section: Introductionmentioning
confidence: 99%
“…Radiotherapy primarily has a role in palliation, but has been suggested as an adjuvant to surgery and chemotherapy in multimodality treatment. 13 15 Combination chemotherapy with pemetrexed and cisplatin has remained unchanged as the standard of care since 2003 following a phase III clinical trial demonstrating superiority of the combination over cisplatin alone (median survival 13.3 months vs 10 months). 19 In 2016, a phase III trial of the antivascular endothelial growth factor (anti-VEGF) recombinant antibody, bevacizumab, in combination with standard chemotherapy was shown to increase survival in comparison to chemotherapy alone (18.8 months vs 16.1 months) across all MPM subtypes.…”
Section: Introductionmentioning
confidence: 99%
“…Malignant pleural mesothelioma (MPM) is a malignant tumor that originates from mesothelial cells and has an extremely poor prognosis [1][2][3][4]. Although MPM is rarer compared to lung cancer, the number of patients worldwide is predicted to increase in the next decades [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Malignant pleural mesothelioma seldom causes metastasis to other organs but has already progressed widely at the time of diagnosis, and radical surgery is often impossible. However, the clinically available therapies for MPM are extremely limited with few regimens [3,4,8]. Therefore, the development of new therapies for unresectable MPM, especially molecularly targeted ones, is highly desirable.…”
Section: Introductionmentioning
confidence: 99%
“…Diagnosis is based on testing of multiple immunohistochemical (IHC) markers of biopsies or cytological samples, and soluble biomarker analysis of pleural effusion to distinguish MPM from other lung malignancies [ 9 ]. The optimal treatment is surgery in combination with chemotherapy and radiotherapy, or both [ 10 ]. Most patients present with a pleural effusion as first symptom and cytological diagnosis increases the chance for earlier diagnosis and prolongs patient survival [ 11 ].…”
Section: Introductionmentioning
confidence: 99%